Anxiety level related to environmental factors in two public dental services: hospital and universitary - Cirilo Jacobo, Jean Paul (2012)
The aim of this study was to compare the levels of dental anxiety in patients who visited dental offices in two public services. Information was obtained from patients who had visited their dentists at least once the present year. The sample size was 100 patients (50 per service). Applying the Corah’s Dental Questionnaire, it was established that 39 % of patients presented moderate anxiety, 19 % in universitary service and 20 % in hospital service; 15 % of the patients presented severe anxiety, 9 % in hospital service and 6 % in universitary service. A great percentage of moderate, high and severe anxiety was perceived in hospital service. Applying the Dental Concerns Assessment, it was concluded that time and costs invested on dental attention are the factors that cause more anxiety in patients among others considered.